Prinsip-prinsip Metode Dakwah menurut Al-Qur’an - Aliyudin, Aliyudin (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2014)
The method of da'wah is one element of da'wah process that has important and strategic role for the success of da'wah acitivies. Methods of da'wah has increase constantly in line with the situation and the condition of its scope. However, the Koran laid the foundation of standardized with respect to the principles that must be built in a variety of methods of propaganda. This principle in which contained in the Qur'an al-Nahl verse 125 : al-Hikmah (wisdom) al-mauidzah al-hasanah (good examplary), and al-Mujadalah al-ahsan (debate with the best way), then actualized and reinforced with the principles of da'wah performed by Prophet Muhammad (peace be upon him).